Antioxidants in neuropsychiatric disorder prevention: neuroprotection, synaptic regulation, microglia modulation, and neurotrophic effects - Liu, Fangfei; Bai, Qianqian; Tang, Wenchao; Zhang, Shumin; Guo, Yan; Pan, Shunji; Ma, Xiaoyu; Yang, Yanhui; Fan, Hua (Frontiers in Neuroscience, 2024)
Oxidative stress, caused by an imbalance between the generation of reactive oxygen species (ROS) and the body’s intrinsic antioxidant defenses, plays a critical role in neurodegenerative diseases such as Alzheimer’s, Parkinson’s, and Huntington’s. Beyond these conditions, recent evidence indicates that dysregulated redox balance is implicated in neuropsychiatric disorders, including schizophrenia, major depressive disorder, and anxiety disorders. Preclinical and clinical studies have demonstrated the potential of antioxidants, such as N-acetylcysteine, sulforaphane, alpha-lipoic acid, L-carnitine, ascorbic acid, selenocompounds, flavones and zinc, in alleviating neuropsychiatric symptoms by mitigating excitotoxicity, enhancing synaptic plasticity, reducing microglial overactivation and promoting synaptogenesis. This review explores the role of oxidative stress in the pathogenesis of neuropsychiatric disorders. It provides an overview of the current evidence on antioxidant therapy’s pharmacological effects, as demonstrated in animal models and clinical studies. It also discusses the underlying mechanisms and future directions for developing antioxidant-based adjuvant therapies. Given the limitations and side effects of existing treatments for neuropsychiatric disorders, antioxidant therapy presents a promising, safer alternative. Further research is essential to deepen our understanding and investigate the clinical efficacy and mechanisms underlying these therapies.